Pelatihan Teknik De-eskalasi untuk Keluarga dan Caregiver dalam Menghadapi Pasien dengan Perilaku Kekerasan di RSKD Dadi Makassar - Kamriana Kamriana; Salmah Arafah; Dina Oktaviana; Dewiyanti Dewiyanti; Alwi Alwi; Ernawati Ernawati; Patmawati Patmawati; Suardi Suardi (jurnal ABDIMAS Indonesia, 2025)
Violent behavior is a major challenge in the care of patients with mental disorders, particularly in acute conditions such as schizophrenia and bipolar disorder. Families and caregivers often lack the knowledge and skills needed to handle crisis situations, thereby increasing the risk of injury and patient relapse. The aim of this program was to enhance the capacity of families and caregivers in managing violent behavior through de-escalation technique training. Used was a two-day face-to-face training (May 2–3, 2025) at RSKD Dadi Makassar involving 10 participants. Activities included interactive lectures, group discussions, simulations, and pre- and post-test evaluations. The training materials were designed based on evidence-based practices, covering empathetic communication, emotional regulation, and conflict management strategies. Of the program showed an increase in understanding of de-escalation techniques from 30% to 90%, improved conflict response ability from 20% to 80%, and a reduction in violent incidents from 12 to 4 occurrences in the week following the training. All participants also expressed satisfaction with the training. De-escalation technique training proved effective in increasing the preparedness of families and caregivers in dealing with violent behavior in patients with mental disorders. This approach is essential for creating a safer, more humane, and recovery-oriented care environment